DAMPAK POLIGAMI TERHADAP PEMENUHAN HAK-HAK ISTRI YANG SAH PADA PERKAWINAN BERDASARKAN KOMPILASI HUKUM ISLAM - Elsa, Marisa; Bachtiar, Maryati; Fitriani, Riska (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Hukum, 2018)
Marriage has a very important and sacred meaning in human life and is a culturalpattern to control and shape the population of life in society. But today, marriage is oftenregarded as not sacred anymore. Because there are some people who use marriage for agood cause. such irregularities such as the men who do polygamy.Polygamy is basically not a bad thing, if done in accordance with the rules andguidance of religion. But most of today polygamy is used as a gap for the fulfillment ofirresponsible male desires and other personal interests. The act of polygamy certainly has agood effect for both men and women. in this thesis the authors wanted to raise about the lossreceived by the wife because it is not in full of the rights of the legal wife who has been inpolygamy by her husband.This thesis, the author will discuss about How is the view of Islamic law and positivelaw about the rights of the legal wife in polygamous marriage? And What are the effects ofthe unenforceability of legitimate wife rights in a polygamous marriage? In this thesis theauthors use research methods of sociological research can be grouped into researchobservational research by survey.The research that has been done in the field with the informant who is the legal wifeof polygamy can be concluded that most of the rights of legal wives that have been regulatedin legislation are in fact not fulfilled, so the concept of fairness in marriage polygamy will notexist if between rights and obligations are not filled with one another.Keywords: Impact - Polygamy marriage - Legitimate Wife Rights